China potencia económica y comercial: una mirada desde el Perú - Fairlie Reinoso, Alan (2015)
This paper analyzes the role of China in the current world situation and its position in the global economy. It also describes China’s foreign policy, and its participation in the international forums. The characteristics of the bilateral trade relationship with Peru are examined, and the investments from China are discussed, including the key sectors that involves and itsimplications in national economy.